Risk factors that influance incidence of neonatal asphyxia - Arumawati, Dwi Yuniar Putri; Santoso, Sabar; Widyastuti, Yani (Jurnal Kesehatan Ibu dan Anak, 2020)
The incidence of asphyxia can have an impact on infant mortality due to factors such as mother, fetus, and childbirth. There was an increase in cases of Sleman Regional Hospital from 12.2% (2017) to 24.2% (2018). The objective of this study was to determine the risk factors that influence the incidence of asphyxia. The research used a control case design. The population of all newborns in Sleman Regional Hospital and the sample was 70 asphyxia and 70 non-asphyxic babies. Research time was August 2019-May 2020. Sampling used consecutive sampling. The variables studied were maternal age, parity, amniotic fluid, premature rupture of membrane (PROM), birth weight, and prematurity. Data were analyzed univariate, chi-square test, and logistic regression. The proportion of asphyxia babies, most of the subjects, were at the age of the mother who was not at risk (74.3%), parity at risk (61.4%), clear amniotic fluid (68.6%), not PROM (74.3%), not LBW (67.1%) and not premature (67.1%). Meanwhile, infants who were not asphyxia, almost all subjects were at the age of the mother who was not at risk (78.63%), parity at no risk (58.6%), clear amniotic fluid (90.0%), not PROM (80%), not LBW (84.3%), and not premature(91.4%). The variables associated with the incidence of asphyxia were parity(p-value 0.028; OR 2.252; 95% CI 1.145-4.429)); meconium in the amniotic (p-value 0.004; OR 4.125; 95% CI 1.628-10.452); birth weight (p-value 0.03; OR 2.625; 95% CI 1.163-5.926) and prematurity (p-value 0.001; OR 5.220 95%;CI 1,971-13,827). Maternal age (p-value 0.690; OR 1.269 95%; CI 0.580-2.777) and PROM (p-value 0.546; OR 1.385 95%; CI 0.626-3.063) were not related. The most dominant factor was prematurity (p-value 0,000; OR: 8.549; 95% CI 2.947-24.800). The incidence of asphyxia was influenced by parity, meconium in the amniotic fluid, birth weight, and prematurity. Meanwhile, maternal age and PROM did not affect the incidence of asphyxia.